Mannose inhibits Plasmodium parasite growth and cerebral malaria development via regulation of host immune responses - Lv, Li; Xu, Zihao; Zhao, Meichen; Gao, Jian; Jiang, Rumeng; Wang, Qian; Shi, Xiaoyu (Frontiers in Immunology, 2022)
D-mannose can be transported into a variety of cells via glucose transporter (GLUT), and supraphysiological levels of D-mannose impairs tumor growth and modulates immune cell function through mechanisms such as interference with glycolysis and induction of oxidative stress. Blood-stage Plasmodium mainly depends on glycolysis for energy supply and pathological immune response plays a vital role in cerebral malaria. However, it is not clear whether mannose affects malaria blood-stage infection. Here, we fed D-mannose to Plasmodium berghei-infected mice and found weight loss and reduced parasitemia without apparent side effects. Compromised parasitemia in C57BL/6 mice was accompanied by an increase in splenic macrophages compared to an untreated group. When mannose was applied to a rodent experimental cerebral malaria (ECM) model, the incidence of ECM decreased. Expression of activation marker CD69 on T cells in peripheral blood and the brain were reduced, and cerebral migration of activated T cells was prevented by decreased expression of CXCR3. These findings suggest that mannose inhibits Plasmodium infection by regulating multiple host immune responses and could serve as a potential strategy for facilitating malaria treatment.